2021
DOI: 10.1007/s43546-021-00173-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of the predictors of government tax revenue in Nigeria

Abstract: Despite Nigeria being Africa's largest economy, it has one of the lowest taxes to Gross Domestic Product (GDP) ratios globally estimated at 6 percent. Although tax revenue is generally low among the states in Nigeria, disparities are noticeable in different parts of the country. The understanding of "what" accounts for the variation in tax revenue and "where" are vital for place-based policy intervention to stimulate tax revenue generation. To this end, this study examines how the geographical differences in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In other words, poverty tends to increase with an increasing distance to the coast. Empirical evidence has shown that locations near the coast have a higher level of economic development because coastal locations favor industrial growth and commercial activities (Adeleke, 2022). According to Adeleke (2022), coastal locations in Nigeria's southern states benefit from trade advantages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, poverty tends to increase with an increasing distance to the coast. Empirical evidence has shown that locations near the coast have a higher level of economic development because coastal locations favor industrial growth and commercial activities (Adeleke, 2022). According to Adeleke (2022), coastal locations in Nigeria's southern states benefit from trade advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence has shown that locations near the coast have a higher level of economic development because coastal locations favor industrial growth and commercial activities (Adeleke, 2022). According to Adeleke (2022), coastal locations in Nigeria's southern states benefit from trade advantages. For instance, the southern states account for more than half of the FDI inflows into the country, and this has positively impacted the local economy and standard of living.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulatory framework surrounding telemedicine in Nigeria is a subject of debate among scholars. Adeleke and Oyekola (2018) argue that a clear and comprehensive regulatory framework is essential to ensure the ethical and secure practice of telemedicine in the country (Adeleke et al, 2021). Grated that the global healthcare landscape has witnessed a paradigm shift towards the integration of emerging web technologies to enhance medical practices, within the context of Nigeria, the adoption of these technologies, particularly in the realms of patients monitoring devices and telemedicine, remains relatively slow among medical doctors.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…In this sense, a technological artifact will be stabilized in its final form only when it is considered satisfactory by all social groups, i.e., the controversies over the conflicting images of the state, citizens and the market are resolved, therefore, when all relevant social groups see the problem of technological inclusion solved, the closure is said to be rhetorical of the technological problem (Lagoarde-Segot & Currie, 2018;Adeleke, 2021).…”
Section: Ethics and Financial Inclusionmentioning
confidence: 99%